2001
DOI: 10.1159/000056261
|View full text |Cite
|
Sign up to set email alerts
|

A Twin Study of Alexithymia

Abstract: Background: Factors contributing to the development of alexithymia and the nature of alexithymia’s relation with trait negative and positive affectivity are unclear. In this study, a twin approach was used to examine the degree of genetic and environmental contributions to the different facets of alexithymia, and the nature of their relations to trait negative and positive affectivity. Method: Forty-five monozygotic and 32 same-sex dizygotic twin pairs completed the Toronto Alexithymia Scale-20, the Eysenck Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 40 publications
8
48
2
Order By: Relevance
“…Jorgensen et al's (2007) large BG study of alexithymia also reported similar results. Although there are some reasons why it might be plausible for shared environmental factors to contribute to individual differences in alexithymia -for example, as noted by Valera and Berenbaum (2001), childhood family factors Note: TAS-20 = Toronto Alexithymia Scale; MZ = monozygotic; DZ = dizygotic; DIF = difficulty identifying feelings; DDF = difficulty describing feelings; EOT = externally oriented thinking. a 2 = additive genetic effects; e 2 = non-shared environmental effects; 95% CI = 95% confidence interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jorgensen et al's (2007) large BG study of alexithymia also reported similar results. Although there are some reasons why it might be plausible for shared environmental factors to contribute to individual differences in alexithymia -for example, as noted by Valera and Berenbaum (2001), childhood family factors Note: TAS-20 = Toronto Alexithymia Scale; MZ = monozygotic; DZ = dizygotic; DIF = difficulty identifying feelings; DDF = difficulty describing feelings; EOT = externally oriented thinking. a 2 = additive genetic effects; e 2 = non-shared environmental effects; 95% CI = 95% confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Using the TAS, Valera and Berenbaum (2001) conducted a small (77 twin pairs in total; 45 MZ and 32 DZ pairs) adult twin study to examine the influence of genetic and environmental factors on the three facets of alexithymia. Results demonstrated that EOT is strongly influenced by genetic factors, but that DIF and DDF are influenced by shared environmental factors.…”
mentioning
confidence: 99%
“…It did not change even if the depressive symptoms alleviated. One potential explanation is that the three factors of alexithymia have different origins in depressed patients, as presented recently [23]. Also other biological explanations, like interhemispheric transfer or right hemispheric specialisation, for personality construct of alexithymia, have to be empirically studied [24].…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis that has been frequently formulated in the literature [9]is that hypertensive patients display difficulties in expressing their emotions (including tension and irritability). In psychosomatic research, these difficulties have often been subsumed under the rubric of alexithymia [33, 34, 35, 36, 37, 38]. In the setting of stressful life circumstances, this may lead to increased sympathetic activation [39]and anxiety sensitivity [40].…”
Section: Discussionmentioning
confidence: 99%